Pengetahuan UMKM Sejahtera Bersama Mengenai Aplikasi Buku Kas - Shafira Dewi Faza; Rival Ardiansyah; Annisa Nur Hanifah; Nabila Rhine Wernada; Natasya Khairunnisa; Aristanti Widyaningsih (Future Science, 2022)
Recording financial reports among UMKM is a problem that often occurs, technological advances which are growing rapidly to date have become a solution to make work easier, one of which is the use of applications. The Cash Book application is here to help business actors in financial records without incurring costs. This program aims to provide knowledge for the owners of the UMKM Sejahtera Bersama about the Cash Book application so that they can assist in problems related to their business financial records. The methods used are observation, interviews, and coordination so that the implementation of the activity process can be easily adjusted. Furthermore, socialization and training regarding the application of the Cash Book were practiced and assisted directly in its implementation. The results of the program show that the UMKM Sejahtera Bersama are able to apply and understand well the use of the Cash Book application and are able to independently input sales data.